Castor Meal and Ground Hydrothermalized Phonolite Optimize Sweet Potato Nutrition, Yield, and Quality - Parecido, Renan J. [UNESP]; Soratto, Rogério P. [UNESP]; Fernandes, Adalton M. [UNESP]; Blanes, Mayara C. [UNESP]; Fidelis, Luis G. [UNESP]; Gitari, Harun I.; Dutra, Sérgio G. (MDPI, 2024)
To assess the effect of pure castor meal and a mixture of castor meal with ground hydrothermalized phonolite rock (CM+HP mixture) in providing nutrients, particularly N and K, and optimizing yield and quality of sweet potato, a field experiment was conducted using a randomized block design. Treatments were the absence and presence of synthetic N and K fertilizers (ammonium nitrate and KCl) combined with rates of organic fertilizers (1.2 and 2.4 Mg ha−1 of castor meal, 2.25 and 4.5 Mg ha−1 of CM+HP mixture, plus a treatment without organic fertilizers). The CM+HP mixture maintained adequate N and K status in plant leaves. Organic fertilizers increased the number of storage roots per plant and the sweetness of the storage roots, while synthetic fertilizers increased the storage root mean weight. Castor meal combined with synthetic fertilizers improved soil health (increased organic matter and enzyme activity in the soil). The combined application of synthetic fertilizers with 2.4 Mg ha−1 of castor meal or 4.5 Mg ha−1 of CM+HP mixture had the greatest benefit on storage root yield, with an average increase of 128% (10.9 Mg ha−1) on marketable storage root yield, and the nutrient removal compared with the sole application of organic fertilizers.
Keywords: hydrothermalized phonolite; Ipomoea batatas; mineral nutrition; organic fertilization; Ricinus communis; storage root yield